Projekt ODEUROPA - Kavčič-Čolić, Alenka (2024)
ODEUROPA is a European research project which bundles expertise in sensory mining and olfactory heritage. This project, whose goal is to show that engaging our sense of smell and our scent heritage is an important means for connecting and promoting Europe’s tangible and intangible cultural heritage, is developing new methods to collect information about smell from both text and image collections. To ascertain how ‘smell’ was expressed in different languages, with what places it was associated, what kinds of events and practices it characterized, and to what emotions it was linked, researchers, analysing circa 30,000 images and 62,000 historical European texts in six languages (English, German, French, Dutch, Italian, and Slovene), are making use of several state-of-the-art AI techniques. Information gathered is stored in the ‘European Olfactory Knowledge Graph’ (EOKG), and then drawn on to create new ‘storylines’ informed by cultural history research.The digital collection before you consists of more than 5,000 textual digital objects, contributed to the ODEUROPA project by the National and University Library and other cultural heritage institutions.
ODEUROPA is a European research project which bundles expertise in sensory mining and olfactory heritage. This project, whose goal is to show that engaging our sense of smell and our scent heritage is an important means for connecting and promoting Europe’s tangible and intangible cultural heritage, is developing new methods to collect information about smell from both text and image collections. To ascertain how ‘smell’ was expressed in different languages, with what places it was associated, what kinds of events and practices it characterized, and to what emotions it was linked, researchers, analysing circa 30,000 images and 62,000 historical European texts in six languages (English, German, French, Dutch, Italian, and Slovene), are making use of several state-of-the-art AI techniques. Information gathered is stored in the ‘European Olfactory Knowledge Graph’ (EOKG), and then drawn on to create new ‘storylines’ informed by cultural history research.The digital collection before you consists of more than 5,000 textual digital objects, contributed to the ODEUROPA project by the National and University Library and other cultural heritage institutions.